ANALISIS PERBEDAAN INFORMASI ANATOMI ANTARA PHASE ENCODING DIRECTION ANTERIOR-POSTERIOR DAN SUPERIOR-INFERIOR MRI LUMBAL T2WI FSE POTONGAN SAGITTAL PADA KASUS HERNIA NUCLEUS PULPOSUS (HNP) DI RUMAH SAKIT HERMINA DEPOK - Patresia, Monicha; Syarif H, Eka Putra; Supriyaningsih, Eny (Jurnal Pendidikan Kesehatan (e-Journal), 2025)
radiographically, Lumbar MRI examination is located in the part of the waist? whereby there is a lot of anatomy one of which is medulla spinalis. In relation to which, in the medulla spinalis area often happen ghosting artifacts which can disturbs the information of Lumbar MRI anatomical image, for that reasons, it needs several numbers of treatments like to apply such a proper phase encoding. In this matter, the application of phase encoding constitutes a possible method which can minimize the artifacts namely by exchanging the direction of phase encoding hence the artifacts is going to the other direction and subsequently the artifacts does not disturb the desired anatomical object.? this research aims to analyze the effect of using the Anterior-Posterior and Superior-Inferior Phase Encoding Direction towards the information of lumbar MRI anatomical image on T2WI FSE sequence of sagittal section undertaken at Hermina Hospital Depok. this research applies quantitative method with analytical approach executed at Hermina Hospital Depok starting from May up to June 2024. Meanwhile, the population of this research is all Lumbar MRI patients with 16 samples which are taken in a purposive sampling basis. As for the method of data collection, it is conducted through among the other things observation and experiment, and then the instrument and analysis of this research are namely worksheet, observation worksheet, questionnaires sheet, documentation, and DVD-R. Thereafter, data processing is carried out by applying statistical test, beginning with normality test. Furthermore to test the hypothesis it is executed by applying Paired Sample T-Test if the data is normally distributed and Test Wilcoxon if the data is not normally distributed. this research suggests that the result of Wilcoxon test, obtains that p-value (0.001) ? 0.05 is for detailed anatomy, p-value (0.000) ? 0.05 is for ghosting artifacts. This matter explains that in the assessment of anatomical details and contrast image, there is a difference between the use of Anterior-Posterior and Superior-Inferior Phase Encoding. Whereas for the evaluation of contrast p-value (0.060) ? 0.05 it can be explained that there is not any difference between the use of Phase Encoding Anterior-Posterior and Superior-Inferior in Lumbar MRI examination T2WI FSE sequence of sagittal section. Apparently, Phase Encoding Anterior-Posterior can provides detail anatomy and ghosting artifacts in more optimal image compared to that in Phase Encoding Superior-Inferior